Testing for Rationality: The Case of Discrete Choice Data - Nunes, Luis Catela (2019)
When working with micro data on consumer demand, there are many different situations where decisions involve only discrete choices. In this context, conditions under which an underlying rational preference structure exists are derived. Moreover, by introducing flexibility into the model, it is possible to identify non rational behavior in the sample.